Kiat Sukses Menulis Jurnal Pada Mahasiswa di Universitas Al-Qolam Malang - Busthomi, Yazidul (Interdisciplinary Explorations in Research Journal, 2026)
Community service is an integral part of the Tri Dharma of Higher Education, its implementation inseparable from the other two Dharma and involves the entire academic community: lecturers, students, education staff, and alumni. Service to the global community, through various collaborative activities with international partners, can be achieved worldwide. Lecturers' duties extend beyond education, including conducting research and developing innovations, as well as preserving and developing superior, beneficial knowledge for the community. Therefore, in relation to community service at the Al-Qolam University of Malang, lecturers are mandated with the task of PROVIDING SUCCESSFUL TIPS FOR JOURNAL WRITING FOR STUDENTS AT AL-QOLAM UNIVERSITY OF MALANG. Among the benefits are increasing student awareness and publishing written works.